Penerapan Path Analisis untuk Mengetahui Pengaruh Layanan Keluarga Berencana dan Indeks Pembangunan Manusia pada Penggunaan Metode Kontrasepsi Jangka Panjang dan Fertilitas di Indonesia - Sari, Nurul Puspita; Munir, Ahmad; AT, M.Ramli; Iskandar, Madris (Hasanuddin University, 2024)
The efficacy of nationwide population control initiatives in Indonesia ought to be uniformly dispersed throughout all provinces. The decentralization policies implemented by each local government and regional differences in characteristics have, nevertheless, resulted in substantial discrepancies in TFR across all provinces in Indonesia. The efficacy of long-acting contraceptives is widely acknowledged as the primary prerequisite for mitigating the pace of population growth. In addition to reducing the TFR, the government has established goals for the equitable distribution of family planning programs across Indonesia. The implementation of family planning programs in an equitable manner will impact the birth rate reduction. The objective of this research is to examine the potential impact of contextual elements on fertility reduction via contraceptive methods in Indonesia. The findings of this research indicate that the proportion of women utilizing long-acting contraceptive methods has the most significant impact on TFR reduction in Indonesia, at -0.562. In contrast, the HDI and the number of family planning villages each have an influence of -0.12 and -0.36, respectively, on TFR reduction.